Donor Air Susu Ibu (ASI) dan Permasalahan Hukumnya serta Upaya Pencegahan Terjadinya Hubungan Kemahraman - Sabri Fataruba (SASI, 2019)
Providing exclusive breastfeeding to babies is the duty of a mother, and the baby has the right to get exclusive breastfeeding from his mother for 6 (six) months, then perfecting it for 24 (twenty four) months or for 2 (two) years. However, not all biological mothers of children born can give breast milk to their children for various reasons. Therefore another mother is required to share (donate) her milk to meet the needs of the child's Mother's Milk. Sharing (donor) Mother's Milk is a noble act, because it can help children whose mothers for certain reasons cannot breastfeed their children. The legal provisions governing Mother's Milk donors are regulated in positive law as well as Islamic Law which is referenced from the word of Allah SWT, the hadith of the prophet Muhammad and Jumhur Ulama. A sincere effort to help other people's children to get Mother's Milk intake should be done by always paying attention to the applicable legal rules, because specifically for those who are Muslim according to their religious law, Mother's Milk donors can have implications for the occurrence of a relationship of friendship. To prevent the occurrence of marriage (marriage) due to the occurrence of the relationship of beauty, there needs to be synergy between government institutions, in this case the Ministry of Health, Ministry of Social Affairs, Ministry of Home Affairs, and Ministry of Religion. The manifestation of this synergy is in the form of policies (regulations) that must be immediately issued in accordance with the existing authority in each of these institutions which in essence is an effort to prevent the occurrence of marriage (marriage) due to the occurrence of the relationship of beauty. The policy (regulation) is a synergy between government institutions, in addition to preventing the occurrence of marriage (marriage) between certain people because of the relationship, also to prevent prospective Mother's Milk donors who have the disease, participate in donating breast milk so that endanger the health of the recipient donor